Total nitrogen of the sediment core EN20001 from Lake Khamra, Yakutia, Siberia - Kathleen Rosmarie Stoof-Leichsenring; Amelie Stieg; Boris K Biskaborn; Izabella Baisheva; Jens Strauss; Justin Lindemann; Luidmila A Pestryakova; Ulrike Herzschuh (PANGAEA, 2025)
This data is an extension to the previously published data of Stoof-Leichsenring et al. (2024), including 23 additional measurements of total nitrogen (TN) from sediment samples of the sediment core EN20001, from Lake Khamra. Nitrogen was determined with an Elementar rapid MAX N exceed, with a measurement accuracy of 0.1 %. Analyses were performed at the AWI Potsdam.